Laboratory Methods for Determining Etiology of Neonatal Infection at Population-based Sites in South Asia: The ANISA Study. Issue 5 (May 2016) - Saha, Samir K.; Islam, Mohammad Shahidul; Qureshi, Shahida M.; Hossain, Belal; Islam, Maksuda; Zaidi, Anita K.; Modak, Joyanta K.; Al-Emran, Hasan M.; Diaz, Maureen H.; McGee, Lesley; Winchell, Jonas M.
Abstract : Background: The Aetiology of Neonatal Infection in South Asia (ANISA) study aims to determine the etiology of neonatal infections in 5 population-based sites in Bangladesh, India and Pakistan. Methods: The main laboratory challenges in ANISA were selection and consistent implementation of laboratory methods at participating sites with varied infrastructure. The other specific challenges included (1) specimen collection and transport to designated study laboratories and timely processing in rural settings; (2) minimal or nonexistent laboratory facilities at the field sites; (3) obtaining sufficient volumes of blood from enrolled infants aged 0–59 days and (4) caregivers' concerns about collection of clinical specimens from young infants. An additional challenge was selecting an appropriate molecular platform from multiple available options, all with limited field validation, for use in determining infection in young infants. Conclusions: This article describes how the challenges of specimen collection, transport and processing and implementation of laboratory methods have been addressed in the ANISA study. It also describes the measures taken to improve detection of microorganisms causing young infant infections by enhancing the sensitivity of existing laboratory methods for pathogen detection.